2019
DOI: 10.3389/fphys.2019.01210
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Physical Activity and Metabolic Control in People With Type 1 Diabetes Mellitus

Abstract: BackgroundThe aim of presented cross-sectional study was to determine the association of different types of physical activity (PA) with metabolic control in people with type 1 diabetes.Materials and MethodsA total of 109 adult subjects with type 1 diabetes were asked to complete the non-exercise activity thermogenesis (NEAT) questionnaire, the hypoglycemia questionnaire, and the World Health Organization Global PA Questionnaire (GPAQ) which was used to assess moderate PA (MPA) and vigorous PA (VPA).ResultsNEAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…High-intensity interval training induced an increased oxidative capacity of skeletal muscle and blunts the rates of glucagon breakdown, which could be a possible protective effect against hypoglycemia after exercise [139]. However, a recent study published by Štotl et al [140], conducted in a cohort of 109 T1DM patients, demonstrated that physical activity in leisure time did not affect glycemic control measured and glycated hemoglobin in T1DM individuals.…”
Section: Exercise Training For the Management Of Diabetes Mellitus: Cmentioning
confidence: 98%
“…High-intensity interval training induced an increased oxidative capacity of skeletal muscle and blunts the rates of glucagon breakdown, which could be a possible protective effect against hypoglycemia after exercise [139]. However, a recent study published by Štotl et al [140], conducted in a cohort of 109 T1DM patients, demonstrated that physical activity in leisure time did not affect glycemic control measured and glycated hemoglobin in T1DM individuals.…”
Section: Exercise Training For the Management Of Diabetes Mellitus: Cmentioning
confidence: 98%